THE INFLUENCE OF SCHOOL ENVIRONMENT ON THE FORMATION OF RELIGIOUS VALUES IN MAN 1 MOJOKERTO - Fitrianah, Alfina R.; Yuliandini, Liza A.; Maharani, Tiara P.; Suliha, Suliha; Firlyandita, Marsyanda; Kusumastuti, Erwin (LP2M IAI Al-Khairat Pamekasan, 2024)
This study focuses on Madrasah Aliyah Negeri (MAN) 1 Mojokerto, to understand how the school environment, particularly student’s perceptions, plays a role in shaping their religious values. A survey method with questionnaires was used to collect data from students in grades X, XI, and XII at MAN 1 Mojokerto. Data analysis was conducted to identify school environment factors that influence the formation of student’s religious values. The results showed that the school environment has a significant role in shaping student’s religious values, which is influenced by religious education policies that support comprehensive and meaningful religious education, a religious curriculum that is relevant, interesting, and encourages understanding and practicing religious values, a school social environment that is conducive to learning and discussing religious values, and the role of teachers and staff who are role models and provide good examples in practicing religious values. This research confirms that the school environment has a strong impact on the formation of student’s religious values. The results of this study make an important contribution to understanding the process of forming religious values in the school environment and opening up the possibility of religious values formation.